2001
DOI: 10.1111/j.1151-2916.2001.tb00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Structural Fe(III) and Iron Oxide Nanophases in Mullite Coloration

Abstract: Six mullite samples, derived from heat-treated natural kaolinites with various iron content, were investigated and compared to synthetic monophasic mullite. They were analyzed by X-ray diffraction, diffuse reflectance spectroscopy, and electron paramagnetic resonance. To quantify mullite coloration, the CIE colorimetric system was used. In contrast to synthetic mullite, samples showed charge transfer bands involving O 2؊ and Fe 3؉ ions as well as ferric crystal-field transitions due to Fe 3؉ ions in iron oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The results of Djemai et al 2001) and Soro et al (2001) that that added iron promotes the growth of the size of mullite conforms previous observation of Grofcsik and Tamas (1961). Moreover, iron is found to absorb during heating and formation of metakaolin.…”
Section: Effect Of Iron and Titanium Oxide On Decomposition Of Kaolinsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of Djemai et al 2001) and Soro et al (2001) that that added iron promotes the growth of the size of mullite conforms previous observation of Grofcsik and Tamas (1961). Moreover, iron is found to absorb during heating and formation of metakaolin.…”
Section: Effect Of Iron and Titanium Oxide On Decomposition Of Kaolinsupporting
confidence: 92%
“…The EPR and Mossbauer spectroscopic results of Djemai et al (2001) and Soro et al (2001) indicated the following role of iron oxide catalyst on mullitization.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Takashima 33 studied the behaviour of Cr 3+ and Fe 3+ ions in the gahnite crystallized from zinc opaque glazes and showed that almost all the Fe 3+ ions migrated into the gahnite (zinc-spinel) phase. Djemai et al 34 postulated that the increased whiteness of mullite samples, which contain iron oxide impurities, by iron incorporation into mullite structure.…”
Section: Discussionmentioning
confidence: 99%